Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium